Observed trends in full-daytime and part-daytime thermal stress conditions in Asia - Yechao Yan; Yangyang Xu; Shuping Yue (Environmental Research Letters)
Changes in environmental thermal conditions affect thermal comfort, work performance and human health. While many studies have focused on heat and cold extremes, which are typically stressful throughout the daytime hours, fewer have examined part-daytime thermal stress conditions, where hours of thermal comfort and discomfort both occur during the daytime. Using a recently developed dataset of the Universal Thermal Climate Index with high spatial (10 km) and temporal (hourly) resolution, we classify daytime outdoor thermal conditions of any day into the following types: full-daytime comfortable, full-daytime stressful (subdivided into ‘full-daytime cold’ and ‘full-daytime hot’), and part-daytime stressful (including ‘part-daytime cold,’ ‘part-daytime cool,’ ‘part-daytime warm,’ ‘part-daytime hot,’ and ‘wide thermal fluctuation’). We then analyze their trends and the balance between changes in heat and cold stress over the past three decades in mid- and low-latitude Asia. Here, we demonstrate that overall daytime outdoor thermal conditions have deteriorated in both low- and mid-latitude Asia. A key feature of the changes in low-latitude regions is the substantial increase in the number of full-daytime hot days and a pronounced escalation in heat stress intensity, which may make outdoor activities during the day increasingly uncomfortable and possibly unsafe. In contrast, notable aspects of the shifts in daytime thermal conditions in mid-latitude regions include a decrease in full-daytime comfortable days (conditions ideal for longer activities such as hiking and camping), and a significant rise in part-daytime hot days, which may lead people to favour shorter activities (e.g., morning walks or neighborhood biking).